Immunochip analysis identifies multiple susceptibility loci for systemic sclerosis - Mayes, Maureen D.; Bossini-Castillo, Lara; Gorlova, Olga; Martin, Jose Ezequiel; Zhou, Xiaodong; Chen, Wei V.; Assassi, Shervin; Ying, Jun; Tan, Filemon K.; Arnett, Frank C.; Reveille, John D.; Guerra, Sandra; et al. (American Journal of Human Genetics, 2014)
In this study, 1,833 systemic sclerosis (SSc) cases and 3,466 controls were genotyped with the Immunochip array. Classical alleles, amino acid residues, and SNPs across the human leukocyte antigen (HLA) region were imputed and tested. These analyses resulted in a model composed of six polymorphic amino acid positions and seven SNPs that explained the observed significant associations in the region. In addition, a replication step comprising 4,017 SSc cases and 5,935 controls was carried out for several selected non-HLA variants, reaching a total of 5,850 cases and 9,401 controls of European ancestry. Following this strategy, we identified and validated three SSc risk loci, including DNASE1L3 at 3p14, the SCHIP1-IL12A locus at 3q25, and ATG5 at 6q21, as well as a suggested association of the TREH-DDX6 locus at 11q23. The associations of several previously reported SSc risk loci were validated and further refined, and the observed peak of association in PXK was related to DNASE1L3. Our study has increased the number of known genetic associations with SSc, provided further insight into the pleiotropic effects of shared autoimmune risk factors, and highlighted the power of dense mapping for detecting previously overlooked susceptibility loci.
EVALuna2:12882